2011
DOI: 10.1016/j.jcrs.2010.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Rotational stability and posterior capsule opacification of a plate-haptic and an open-loop-haptic intraocular lens

Abstract: The 2 IOL models had comparable, excellent rotational stability and low PCO intensity 1 year postoperatively. Thus, the plate-haptic IOL may be a good platform for a toric model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…These results were in agreement with others demonstrating that rotation occurred 1 hour after surgery. 12 The fact that the rotation takes place so quickly suggests that it might be a consequence of poor friction between the haptic and the capsular bag due to an incomplete ophthalmic viscoelastic device clearance, as previously suggested. Alternatively, it could be due to the size difference between the capsular bag and IOL diameter.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…These results were in agreement with others demonstrating that rotation occurred 1 hour after surgery. 12 The fact that the rotation takes place so quickly suggests that it might be a consequence of poor friction between the haptic and the capsular bag due to an incomplete ophthalmic viscoelastic device clearance, as previously suggested. Alternatively, it could be due to the size difference between the capsular bag and IOL diameter.…”
Section: Discussionmentioning
confidence: 85%
“…Neverthe- less, it is important to indicate that these results were in disagreement with those described by Patel et al 23 because they described plate-haptic lenses as more stable in terms of rotation than open-loop haptic lenses. Interestingly, Prinz et al 12 found a similar rotational behavior between both lens designs. Surprisingly, the multifocal design of the AcrySof IQ toric IOL showed 2° more rotation than the monofocal design.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations